KEKANG SUBALTERN DALAM NEGASI MEDIA TENTANG SYIAH: - Muhammad War’Í (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
This paper analyzes some anti-Shia articles which are abundantly available in online media. As a minority group, Shia is in a subaltern position where they were published negatively. This publication created negative paradigm of Shia in the society. In the borderless world of cyberspace, the production of Shia articles appears in the form of unequal semiotic relationships. Quite often, the meaning of Shia was published from the subjective perspective of a particular group. For this reason, this research examines the phenomenon of Shia trending articles from the cyber semiotic perspective. The research revealed that the subaltern bridle against the Shia in the media remains so strong. It requires self-awareness to provide equal opportunity for Shia speak up in the media in a balanced way. By such opportunity, the balanced view on the Shia can be obtained. It is hoped that this objective view could establish inclusivity in religious life.